Mesoporous Co3O4 as a New Catalyst for Allylic Oxidation of Cyclohexene - Hajer Azzi; I. Rekkab-Hammoumraoui; L. Chérif-Aouali; A. Choukchou-Braham (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
Mesoporous cobalt oxide was investigated for the liquid phase oxidation of cyclohexene using tertiobutylhydroperoxide (TBHP) as an oxidant. The results were compared with several series of supported cobalt catalysts to study the influence of the cobalt loading and solvents on the overall conversion and selectivity. Mesoporous cobalt was synthesized through the nanocasting route using siliceous SBA-15 mesoporous material as a hard template and cobalt nitrate as the cobalt oxide precursor. Supported cobalt oxide catalysts (Co/MxOy) were synthesized by the impregnation method using two loadings (1 and 5 wt.%) and Al2O3, TiO2, and ZrO2 as supports. Samples were characterised by means: elemental analysis, X-ray powder Diffraction (XRD), BET (surface area), UV-Vis DR Spectroscopy, and MET. The results obtained showed that the cobalt oxide retains the mesoporous structure of SBA-15, and in all Co/MxOy, crystalline Co3O4 and CoO phases are observed. The mesoporous cobalt oxide is more active than the supported cobalt catalysts in the allylic oxidation of cyclohexene, with a conversion of 78 % of cyclohexene and 43.3 % selectivity toward 2-cyclohexene-1-ol. The highest activity of mesoporous cobalt oxide could be ascribed to its largest surface area. Furthermore, Co3O4 has both Lewis and Brönsted acidic sites whereas Co/MxOy has only Lewis acidic sites, which could also explain its superior catalytic activity. Moreover, mesoporous cobalt oxide was more stable than supported cobalt catalysts. Therefore, this catalyst is promising for allylic oxidation of alkenes.